2010
DOI: 10.1007/s00223-010-9351-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the PTH Gene, Hip Fracture, and Femoral Neck Geometry in Elderly Women

Abstract: Running title: PTH gene and hip geometry 2(25) ABSTRACT Purpose: Parathyroid hormone (PTH) is a principal regulator of calcium homeostasis.Previously, we studied single nucleotide polymorphisms (SNPs) present in the major genes in the PTH pathway (PTH, PTHrP, PTHR1, PTHR2) in relation to bone mineral density (BMD) and fracture incidence. We found that haplotypes of the PTH gene were associated with fracture risk independent of BMD. In this present study, we evaluated the relationship between PTH haplotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…To minimize variability, all variables were analyzed by a single operator. The coefficient of variation for these measurements was between 0.6 and 3.7% [49].…”
Section: Methodsmentioning
confidence: 92%
“…To minimize variability, all variables were analyzed by a single operator. The coefficient of variation for these measurements was between 0.6 and 3.7% [49].…”
Section: Methodsmentioning
confidence: 92%
“…Tenne et al [30] investigated whether the SNPs within PTH play a role in femoral neck geometry and bone quality in 750 elderly women aged 75 years. They showed that carriers of haplotype 9 had lower values for hip geometry parameters suggestive of increased fracture risk: cross-sectional moment of inertia (p = 0.029), femoral neck width (p = 0.049), and section modulus (p = 0.06).…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…However, a recently published study by Leslie et al in the Manitoba cohort provides the first evidence that HAL is also predictive of incident hip fracture in both men and women, independent of BMD or FRAX [117]. Like HLA, NSA, and other hip geometry parameters including buckling ratio and section modulus have been found to predict hip fracture in postmenopausal Caucasian women [114, 118121]. However, to date, it is not yet clear if this risk is independent of BMD.…”
Section: Introductionmentioning
confidence: 99%